OpenCourseWare, Global Access and the Right to Education: Real access or marketing ploy? - Huijser, Henk Johannes; Bedford, Tas; Bull, David (International Review of Research in Open and Distributed Learning, 2008)
This paper explores the potential opportunities that OpenCourseWare (OCW) offers in providing wider access to tertiary education, based on the ideal of ‘the right to education’. It first discusses the wider implications of OCW, and its underlying philosophy, before using a case study of a tertiary preparation program (TPP) at the University of Southern Queensland (USQ) to draw out the issues involved in offering a program that is created in a particular national and social context on a global scale. This paper draws specific attention to the digital divide, its effects in national and global contexts, and the particular obstacles this presents with regards to OCW. This paper argues that OCW provides many opportunities, both in terms of access to education and in terms of student recruitment and marketing for universities. To take full advantage of those opportunities, however, requires a concerted effort on the part of tertiary education institutions, and it requires a vision that is fundamentally informed by, and committed to, the principle of ‘the right to education’.